"#Australia in the morning, #Thailand by midday, #America in the afternoon": Global mobility in MNC employer branding messages on Facebook. Issue 1 (8th April 2020) - Ellmer, Markus; Reichel, Astrid; Naderer, Sebastian T.
Abstract : Purpose: The purpose of this paper is to generate insights into how multinational companies (MNCs) promote global mobility in their Employer Branding (EB) messages on Facebook. Design/methodology/approach: The authors analyzed 13.340 EB messages found on the Facebook career pages of 30 major MNCs (10 of each in the US, UK and Germany) drawing on a methodological approach combining Grounded Theory and text-mining. Findings: Building on the perspective of psychological contracts as sensitizing concept, the analysis of the overall sample reveals a range of core themes in EB messages across all MNCs studied. With regards to global mobility, MNCs emphasize relational, i.e. socio-emotional, contents, particularly, highlighting opportunities of experience and personal development. While global mobility is an overall marginal theme, German MNCs extensively promote global mobility, whereas US- and UK-based MNCs do not explicitly make it a subject of their messages. The findings are discussed in the light of institutional theory. Originality/value: Despite mega-trend, little is known about social media EB, especially when it comes to the contents that MNCs communicate to (potential) employees. Applying an innovative methodological approach, the authors offer insights into these contents. Discussing the findings in the light of institutional theory, it is concluded that promoting global mobility in socio-emotional terms seems of high importance to reduce uncertainties associated with living and working abroad. This might help firms to hire internationally mobile employees, especially in countries where job mobility is generally low.